Nostradamus : prophecies for women - Lorie, Peter (New York, NY Simon & Schuster, 1995)
Relates the predictions of Nostradamus regarding women and their power at the end of the twentieth century
D., 12/02
Keywords: Nostradamus, 1503-1566; Prophecies (Occultism); Women--Social condition--Forecasting; Twenty-first century--Forecast